Professional-applied physical training students by means of field hockey - Pylypey L.P; Shapoval N.S (Kharkov National Pedagogical University, 2010)
Description of the modern crisis state of health and physical preparedness of graduating students of higher institutes is resulted. Most graduating students can not high-quality work on a production. Not efficiency of the existent system of physical education is rotined in the institutes of higher. The terms of intensification of educational process are considered. Efficiency and forming actuality is investigational for the students of motivation to the select kind of sport (field hockey). The stages of introduction of innovative approaches, new credit-module technologies in the river-bed of the Bologna system are presented.